Parallax techniques in presentations ceremonial theatre Ibn al-Rumi in the shanty towns (a model) (Journal of the College of Basic Education, 2022)
The theatrical scene has undergone many technical developments in different eras and varied in each time period, as the design and composition of the view stems from the shape of the space, whether it is open or closed. The first is the theatrical phenomenon. We also find in the religious ceremonies of the inhabitants of the Nile Valley a ritual similarity, but as a result of the lack of conclusive evidence of the existence of these manifestations as a theatrical genre, it has become impossible to determine the aesthetic specificity of drawing the theatrical features of these two civilizations. in its religious approach